Exploring DHHers experience influencing factors in multimedia-based driving training through a service design study - Linxin Zheng; Jing Ran; Chenwen Wo; Yujie Xin; Zui Tao; Renke Jin (Acta Psychologica, 2025)
Deaf and hard-of-hearing individuals (DHHers) have the right to learn to drive and obtain driving licenses. However, it is not friendly for them to learn to drive in China. Society and scholars have paid little attention to this phenomenon. This study aims to identify the critical factors influencing the training experience of deaf and hard-of-hearing individuals and proposes strategies for optimizing driver training services through multimedia technology. First, we explored the factors affecting the quality of DHHers driving training services through grounded theory, interview with DHHers (n = 20), and service design, as well as the current situation and strategies of multimedia technology to improve training services. Following this, we propose a driving training service process incorporating multimedia technology and conducted a simulation experiment for DHHers' driving training (n = 41) to examine multifactorial coupling and causality through questionnaire-based research. Based on Bayesian Structural Equation Modeling (BSEM) to validate a model of user experience and influencing factors, the results show that (1) social support, technology support, communication efficiency, training efficiency, environment construction, and emotional support together determine the experience of DHHers in driving training; (2) personal factors moderated the effects of training efficiency, environment construction, and emotional support on experiential feelings. Based on the analysis of the results, this study proposes six strategies for driving training service design for DHHers people in China, which aims to enhance their quality of life and employment perspectives. Finally, we explored the implications of service quality and proposed strategies for multimedia technology to enhance the current landscape of driver training for DHHers individuals. It also provides a development path for digitally barrier-free design and service systems.